Parameter study, antioxidant activities, morphological and functional characteristics in microwave extraction of medicinal oleoresins from black and white pepper - Olalere, Olusegun Abayomi; Nour, A. H.; R. M., Yunus; Alara, Oluwaseun Ruth; Ahmad, Mani Malam; Yasmeen, Hafiz Zaki; Abdlrhman, Hybat Salih Mohamed (Taylor & Francis, 2018)
The study investigated the effects of extraction parameters on the yield, antioxidant activities, morphological and functional group characteristics of black and white pepper oleoresin extracts. Optimized oleoresin yields of 5.64 and 8.72 w/w% were obtained as black and white pepper extracts, respectively. Moreover, from the antioxidant assay, the concentration of black and white pepper extracts required to scavenge half of stable DPPH radicals were 94.92 and 107.57 µg/ml, respectively. From the complementary antioxidant assay; the concentration of black and white pepper extracts required to scavenge half of the stable ABTS free radicals were 82.36 and 94.71 µg/ml, respectively. This indicated that extracts from white pepper exhibited higher antioxidant capacity than the black pepper extracts. The results from the untargeted compositional GC-MS analysis identified a total of 23 and 31 bioactive compounds in black and white oleoresin extracts, respectively. This study, therefore, revealed the potential of microwave extraction in obtaining high-quality extracts.